Reefs under Siege—the Rise, Putative Drivers, and Consequences of Benthic Cyanobacterial Mats - Ford, Amanda K.; Bejarano, Sonia; Nugues, Maggy M.; Visser, Petra M.; Albert, Simon; Ferse, Sebastian C. A. (Frontiers in Marine Science, 2018)
Benthic cyanobacteria have commonly been a small but integral component of coral reef ecosystems, fulfilling the critical function of introducing bioavailable nitrogen to an inherently oligotrophic environment. Though surveys may have previously neglected benthic cyanobacteria, or grouped them with more conspicuous benthic groups, emerging evidence strongly indicates that they are becoming increasingly prevalent on reefs worldwide. Some species can form mats comprised by a diverse microbial consortium which allows them to exist across a wide range of environmental conditions. This review evaluates the putative driving factors of increasing benthic cyanobacterial mats, including climate change, declining coastal water quality, iron input, and overexploitation of key consumer and ecosystem engineer species. Ongoing global environmental change can increase growth rates and toxin production of physiologically plastic benthic cyanobacterial mats, placing them at a considerable competitive advantage against reef-building corals. Once established, strong ecological feedbacks (e.g. inhibition of coral recruitment, release of dissolved organic carbon) reinforce reef degradation. The review also highlights previously overlooked implications of mat proliferation, which can extend beyond reef health and affect human health and welfare. Though identifying (opportunistic) consumers of mats remains a priority, their perceived low palatability implies that herbivore management alone may be insufficient to control their proliferation and must be accompanied by local measures to improve water quality and watershed management.